Resting salivary levels of IgA and cortisol are significantly affected during intensive resistance training periods in elite male weightlifters - Tsai, M. L.; Li, T. L.; Chou, L. W.; Chang, C. K.; Huang, S. Y.; Fang, S. H. (The Journal of Strength and Conditioning Research, 2012)
The aim of this study was to investigate the cumulative effects of intensive resistance training on salivary immunoglobulin A (SIgA) and cortisol responses in elite male weightlifters. Eleven elite male Taiwanese weightlifters were trained through 3 training stages before a national weightlifting competition, and this was followed by a 2-week recovery stage. Resting saliva samples were collected once in each of the 4 stages. Salivary concentrations of total protein (TP), SIgA, lactoferrin, and cortisol were measured. The results showed that (a) salivary TP concentrations were not significantly affected; (b) resting levels of SIgA, the ratio of SIgA to TP (SIgA/TP), cortisol, and the ratio of cortisol to TP (cortisol/TP) were significantly higher in the training stages than in the recovery stage; (c) a positive correlation was revealed between the ratios of SIgA/TP and cortisol/TP; and (d) the resting salivary lactoferrin concentrations and the ratio of lactoferrin to TP (lactoferrin/TP) were significantly lower in stage 1 than in the recovery stage. The findings in this study suggest that prolonged, intensive resistance training exerts cumulative effects on SIgA and cortisol responses in elite weightlifters.